Unilateral Cervical Polyneuropathies following Concurrent Bortezomib, Cetuximab, and Radiotherapy for Head and Neck Cancer. (25th February 2016) - Elghouche, Alhasan; Shokri, Tom; Qin, Yewen; Wargo, Susannah; Citrin, Deborah; Van Waes, Carter
Abstract : We report a constellation of cervical polyneuropathies in a patient treated with concurrent bortezomib, cetuximab, and cisplatin alongside intensity modulated radiotherapy for carcinoma of the tonsil with neck metastasis. The described deficits include brachial plexopathy, cervical sensory neuropathy, and oculosympathetic, recurrent laryngeal, and phrenic nerve palsies within the ipsilateral radiation field. Radiation neuropathy involving the brachial plexus is typically associated with treatment of breast or lung cancer; however, increased awareness of this entity in the context of investigational agents with potential neuropathic effects in head and neck cancer has recently emerged. With this report, we highlight radiation neuropathy in the setting of investigational therapy for head and neck cancer, particularly since these sequelae may present years after therapy and entail significant and often irreversible morbidity.